FINDINGS AND EVALUATIONS OF CHOLANGIOGRAPHY IN PERCUTANEOUS TRANS HEPATIC BILIARY DRAINAGE PATIENTS IN SIRIRAJ HOSPITAL - KRUATRACHUE, Chutakiat; PRABHASAWAT, Krisdee; CHOOSRI, Kidsada; CHAIYASOOT, Walailak (The ASEAN Journal of Radiology, 2023)
Sixtyseven cholangiographic findings in the films, with clinical histories and investigations of 119 patients in Siriraj Hospital were reviewed by two radiologists. Classifications of causes of obstructive jaundice were devided depending on the anatomical locations and morphologies. Proximal extrahepatic duct obstruction was the most common location (41.8%) and focal stenotic type was mostly founded in the morphologic picture (86.5%). The most founded diagnosis in 119 patients was cholangiocarcinoma (54.6%). There were 61.3% male and 38.7% female patients, with average age of 58.43% years, most of them came with jaundice (99.2%). The total bilirubin was higher than 10 mg./dl. In about 90%, and the CA19- 9 level was higher than 100 U/ml. in about 80%. Comparisons with other previous studies were performed.